Primary Tumor Extension Profiles of T3-T4 Glottic Carcinoma at RSUP Dr. M. Djamil Padang - Aisyah Suci Ayudya; Sukri Rahman; Hasmiwati Hasmiwati (Jurnal Otorinolaringologi Kepala dan Leher Indonesia, 2026)
Primary Tumor Extension Profiles of T3-T4 Glottic Carcinoma at RSUP Dr. M. Djamil Padang Background: Laryngeal carcinoma is a malignant tumor arising from the laryngeal epithelium, and most cases originate from the glottis (60–75%). In Indonesia, laryngeal carcinoma ranks 17th, with approximately 4,000 cases and a mortality rate of 1%. Symptoms of glottic carcinoma are commonly nonspecific, such as hoarseness, and are therefore often overlooked, leading many patients to present at an advanced stage. Treatment selection and prognosis are influenced by the extent of tumor spread to surrounding tissues. Computed tomography (CT) is used to detect invasion and to assist in staging. This study aimed to describe the pattern of primary tumor extension in T3-T4 stage glottic carcinoma at Dr. M. Djamil General Hospital, Padang. Methods: This quantitative study used a descriptive design with a retrospective approach based on medical records. A total of 19 patients with T3-T4 stage glottic carcinoma at Dr. M. Djamil General Hospital, Padang, were included. Data were analyzed using univariate analysis and presented as frequencies and percentages. Results: The most common T stage was T4 (68.4%). In T3 disease, the most frequent extension was invasion of the inner cortex of the thyroid cartilage (71.4%). In T4 disease, the most frequent extension was invasion of the outer cortex of the thyroid cartilage (42.3%). Conclusion: Most advanced-stage glottic carcinomas were T4; the most frequent extension pattern in T3 was invasion of the inner cortex of the thyroid cartilage, whereas in T4 it was invasion of the outer cortex of the thyroid cartilage.